The prevalence of urinary incontinence in aged women in Peguyangan Village, District of Tag-Tag Kelod, Denpasar, Bali - Diviya Batumalay; Yuliana Yuliana; I Nyoman Mangku Karmaya (DiscoverSys Inc., 2019)
Background: Urinary incontinence (UI) is a significant health problem with considerable social and economic impact. Distinguishing between prevalence and incidence of incontinence is important. There are significant variations in the severity and impact of incontinence, and its severity, frequency, and predictability all need to be considered when evaluating its effects on patients, the degree of bother is particularly significant when determining who will need treatment. Incontinence may be a result of bladder dysfunction, sphincter dysfunction, or a combination of both, but large-scale studies are not designed to determine the etiology. Aim: To know the prevalence of UI in aged women in Peguyangan village, Denpasar, Bali.Method: This is cross-sectional descriptive design conducted in Peguyangan Village Denpasar, Bali, in early July 2017. There were 79 of 94 aged women above 65 years involved in the survey using a questionnaire.Result: In young women, the prevalence of incontinence is usually low, but prevalence peaks around menopause, with a steady rise there-after into later life. Although the prevalence of stress and mixed (stress and urge) incontinence is higher than urge incontinence, the latter is more likely to require treatment. In women, moderate and severe bother have a prevalence ranging from about 3% to 17%. Severe incontinence has a low prevalence in young women but rapidly increases at ages 70 through 80.Conclusion: The prevalence is 0.076.